2017
DOI: 10.1021/acs.macromol.7b02237
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Relaxation Dynamics of the Core and Corona in a Single Dry Micelle

Abstract: The segmental relaxation dynamics of the core and the corona in a single dry spherical micelle comprising a polystyrene (PS) or poly­(methyl methacrylate) (PMMA) core and a poly­(acrylic acid) (PAA) corona, along with the effects of the micelle density and the chain length of the core-forming and corona-forming polymers, were investigated by AFM. The results showed that the segmental relaxation temperature in the micelle core was close to its bulk T g and independent of the micellar structure, such as micelle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To estimate the particle diameter, D 0 , one needs to account for the effect of tip broadening. 51,52 As a result of tip broadening, the apparent lateral…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the particle diameter, D 0 , one needs to account for the effect of tip broadening. 51,52 As a result of tip broadening, the apparent lateral…”
Section: Resultsmentioning
confidence: 99%
“…The drop in the scattering intensity was attributed to the decreased refractive index and the morphological deviation from the original sphere geometry. Both are direct consequences of the enhanced molecular mobility. , During the glass transition, the segments of the polymer chain began to move locally and thus increased the free volume in the PSNS, resulting in the reduced material density as well as the refractive index. For example, existing studies by using Mie spectroscopy revealed that the refractive index of polystyrene beads in rubbery state was smaller than that in glassy state .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The thickness of the adsorbed layer was determined by fitting the refractive index measured above to prevent inaccuracy in the measurement of the adsorbed layer thickness caused by the variation of refractive indices (compared to the bulk polymer) on various systems. Atomic force microscopy (AFM, MultiMode-8, Bruker, Billerica, MA, USA) 7,58–60 was adopted to observe the surface morphology of the adsorbed layer. X-ray reflection (XR) was utilized to determine the density distribution of the adsorbed layer.…”
Section: Methodsmentioning
confidence: 99%